Articulação entre disciplinas de uma escola de tempo integral: reverberações de um Grupo de Trabalho Diferenciado (GTD) nas aulas de Matemática - André Augusto Deodato (2017)
The present juncture accentuated the Brazilian citizens demand for the amelioration of public schools. The State recognized this demand to a certain degree by asserting, in the sixth goal of the National Plan of Education 2014-2024, that one way to qualify these schools would be to extend their daily journey, making them full time schools. However, it is possible to observe that in Brazil, historically, some educational systemexpansions have overburdened these institutions making them to embrace new tasks, without the necessary public investment. By weakening the pedagogical work, some of such expansions turn out to be expansions for less. Within such context, this research developed to shed light over the pedagogical work of a full time school with the aim toidentify reverberations of new disciplines in the mathematics classes and to describe how these reverberations unfolded in these classes. Anchored in theoretical and methodological references from the Cultural Historical Activity Theory, an investigation of a qualitative nature was developed in a 7th grade mathematics classroom from a public school of the federal educational system of the State of Minas Gerais. The empirical data was generated throughout the year 2014, in two stages. Stage one was held from April to June 2014, when all the 7th grade mathematics classes were observed, simultaneously with the classes of a discipline entitled Group of Differentiated Work The Man, the Environment and their Interactions. The second stage was held from July to December 2014, when mathematics classes continued underobservation, and the researcher started to lecture a subject entitled Group of Differentiated Work Potentiating Space of Articulations (GTD EPA) with the expectation that it would reverberate in the mathematics classes. The instruments used for the production of data were interviews and field diary. The interactions produced with the research subjects were audio and video recorded. The unit of analysis was restricted to the mathematics classes in which it was possible to characterize an activity,considering its internal dynamics and historical changes. This activity, when analyzed, gave visibility to some tensions caused by the reverberations of the GTD EPA in the mathematics classes. Such tensions were identified especially when the students used, inthe mathematics classes, actions developed in the GTD EPA that clashed with some of the rules established for these classes. From this analysis stands out as a result, from a more specific point of view, that these tensions have shown to contribute to initiate a potentially expansive mini-cycle of learning, when a student started considering in classthe procedure used in the transformation of decimal numbers into fractions and to discuss the convenience of its use, rather than just using it mechanically. On the other hand, also stands out that certain tensions, under some given circumstances, may alienate the subjects from the activity. From a broader point of view, the analysis of the reverberations of the GTD EPA in the mathematics classes revealed that it is possible toenhance articulations between different disciplines of full time schools. However, it also showed that, besides the articulation of the disciplines, the expansion of the students learning is as well influenced by the way the community involved faces the tensions. That is, the articulations alone do not guarantee expansions in the process of learning of the students involved in the articulated disciplines.